Rancang Bangun Aplikasi Pemesanan Pada Cantika Catering Berbasis Web - Sri Muryani; Devie Safika (Universitas Bina Sarana Informatika, 2019)
The system available right now at Cantika Catering is conducted manually, started from recording customer's orders to keep other data related to processes from sales to transactions, keeping the records accurately, and spending less time to search some data. Cantika catering requires information system which can support and deliver satisfactory services for its customers. Therefore, the author tried to compose a research about the sales system in Cantika Catering which was completed by using data collection methods as follows: direct observation, interview, and literature review. Nowadays, Cantika Catering is a business dealing only with food provision service. The design of information system is the best solution to handle problems in this company, and a computerized system will make the company's actvities more effectively and efficiently. Therefore, the researcher has conducted a change of system for Cantika Catering from manual to computerized and web based order transaction